Site-selective labeling at Cys302 of aldehyde dehydrogenase unveils a selective mitochondrial stain - Kim, Yun Kyung; Lee, Jin Kak; Lee, Jun-Seok; Yoon, Chang No; Chang, Young-Tae (ROYAL SOC CHEMISTRY, 2011)
A mitochondria-trackable fluorophore, CDy2, selectively labels Cys302 in the active site of mitochondrial aldehyde dehydrogenase (ALDH2).
Keywords: LIVING CELLS; IN-VIVO; RHODAMINE-123; DISULFIRAM; INHIBITION; PROBE